Efeitos da correlação eletrônica sobre as polarizabilidades longitudinais do polidifluoroacetileno - TORRES, Elber Magalhães (2005)
This work presents ab initio results, including correlation corrections, for the static longitudinal linear polarizability, ®L, and longitudinal second hyperpolarizability, °L, of planar and twisted fluorinated polyacetylene (polyacetylene) chains. These electric properties were calculated by the finite field (FF) method and the correlated energies were obtained by means of the second order MÁller-Plesset perturbation theory (MP2). Our MP2 calculations were performed using the 6-31G basis set, although the geometry optimization involved both, the 6-31G and 6-31G(d) basis sets. Our results show that the incorporation the electron of correlation effects in the calculations of the polarizabilities, specially the hyperpolarizabilities, is essencial in order to obtain reliable estimates of these properties. Our estimates also demonstrate that the substitution of the H atoms in polyacetylene by F atoms, a procedure that gives rise to polydifluoroacetylene (PDFA), has the effect of incrasing the non-linear response of this material.